أثر محددات القطاع الزراعي على الناتج الزراعي في الجزائر خلال الفترة (1990-2022) - السعيد غربي; عبد الرؤوف مهاوات; يونس عبية (جامعة الوادي University Of Eloued, 2024)
"تهدف الدراســــــة الى معالجــــــــــــــــة العلاقــــــة بيــن القطــــاع الزراعي والناتـج الزراعي في الجزائــر خلال الفترة (1990-2022) وقد تم استخدام نموذج المربعات الصغرى المصححة كليا ( (FMOLSلاستخراج العلاقات طويلة الاجل بين متغيرات الدراسة. ونموذج تصحيح الخطأ (ECM) لاستخراج العلاقات في الاجل القصير. وخلصت الدراسة على ان متغيرات القطاع الزراعي تؤثر ايجابيا على الناتج الزراعي في الاجل الطويل وهو ما يتوافق مع النظرية الاقتصادية، في حين التوصل الى انه لا يوجد علاقة بين المتغيرات المستقلة في الاجل القصير " "The Study aims to address the relationship between the agricultural sector and agricultural output in Algeria during the period (1990-2022) The fully corrected least squares model (FMOLS) was used to extract the long-term relationships between the study variables, and the error correction model (ECM) to extract the short-term relationships. The study concluded that agricultural sector variables positively affect agricultural output in the long term, which is consistent with economic theory, while concluding that there is no relationship between the independent variables in the short term. "
Keywords: القطاع الزراعي، الناتج الزراعي، القوى العاملة، المساحة المزروعة.; agricultural sector; agricultural output; labor force; cultivated area.